Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC). - Tjønneland, A; Christensen, J; Olsen, A; Stripp, C; Thomsen, B; Overvad, K; Peeters, P; Gils, v; Bueno-de-Mesquita, H; Ocké, M; Thiebaut, A; Fournier, A; et al. (2007)
OBJECTIVE: Most epidemiologic studies have suggested an increased risk of breast cancer with increasing alcohol intake. Using data from 274,688 women participating in the European Prospective Investigation into Cancer and Nutrition study (EPIC), we investigated the relation between alcohol intake and the risk of breast cancer. METHODS: Incidence rate ratios (IRRs) based on Cox proportional hazard models were calculated using reported intake of alcohol, recent (at baseline) and lifetime exposure. We adjusted for known risk factors and stratified according to study center as well as potentially modifying host factors. RESULTS: During 6.4 years of follow up, 4,285 invasive cases of breast cancer within the age group 35-75 years were identified. For all countries together the IRR per 10 g/day higher recent alcohol intake (continuous) was 1.03 (95% confidence interval (CI): 1.01-1.05). When adjusted, no association was seen between lifetime alcohol intake and risk of breast cancer. No difference in risk was shown between users and non-users of HRT, and there was no significant interaction between alcohol intake and BMI, HRT or dietary folate. CONCLUSION: This large European study supports previous findings that recent alcohol intake increases the risk of breast cancer.